2014
DOI: 10.1063/1.4867175
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Faraday cup signal analysis and the measurement of energetic ions emitted by plasma focus

Abstract: A theoretical model is developed to study the signals from a typical dynamic Faraday cup, and using this model the output signals from this structure are obtained. A detailed discussion on the signal structure, using different experimental conditions, is also given. It is argued that there is a possibility of determining the total charge of the generated ion pulse, the maximum velocity of the ions, ion velocity distribution, and the number of ion species for mixed working gases, under certain conditions. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This effect may have several causes such as (1) existence of ions with several ionization degrees. 22,23 We have modeled the dynamical Faraday cup signals already 24 and shown that this may be the main cause of the signal broadening, (2) the existence of heavy charged impurities (such as Cu ions sputtered from copper anode of PF) can be another cause of broadening. This may be investigated using another diagnostics such as mass or X-ray spectrometry, and (3) other source of signal broadening can be the RC value of the related circuit.…”
Section: Apparatusmentioning
confidence: 99%
“…This effect may have several causes such as (1) existence of ions with several ionization degrees. 22,23 We have modeled the dynamical Faraday cup signals already 24 and shown that this may be the main cause of the signal broadening, (2) the existence of heavy charged impurities (such as Cu ions sputtered from copper anode of PF) can be another cause of broadening. This may be investigated using another diagnostics such as mass or X-ray spectrometry, and (3) other source of signal broadening can be the RC value of the related circuit.…”
Section: Apparatusmentioning
confidence: 99%
“…Dense Plasma Focus (DPF) devices are pulsed sources of neutrons [1][2][3][4][5], electron beams [6-8], soft x-ray radiation (SXR) [9][10][11][12][13][14][15] and ion beams [16][17][18][19][20][21][22][23]. Column of a pinched plasma in a PF device is believed to typically produce pulsed ions from several of 100 keV to several of MeV (considering ions emitted from the nuclear fusion reactions) [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Space-and time-resolved investigation of high energy deuterons emitted from three DPF devices was conducted [33]. Ion beams have been investigated using Faraday Cup (FC) as a diagnostic tool for ion current density alongside ion time-of-ight (ToF) measurements [18][19][20][21][22]. The ion energies are predominantly in the tens to hundreds of keV range, the pulse durations are tens of ns, and the currents are typically tens of kA [34].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] For plasma focus devices, a Faraday Cup (FC) is a very useful diagnostic tool for ion current density and ion time of flight measurements. [7][8][9] The ion energies are predominantly in the tens to hundreds of keV range, the pulse durations are tens of ns, and the currents are typically tens of kA. 10,11 The velocity, energy, and density of nitrogen ions have been estimated using the FC TOF technique in a plasma focus device by Mohanty in 2005.…”
Section: Introductionmentioning
confidence: 99%